CONTESTING THE AUTHENTICITY OF ABU HURAIRAH’S MISOGYNISTIC HADITH: Bennett and Mernissi’s Critical Perspectives - Sulis Nuriyawati; Muhid Muhid; Isnaini Lu’lu Atim Muthoharoh (Riwayah: Jurnal Studi Hadis, 2025)
The critique of Prophet Muhammad’s originality, both historical and theological, has long been a central concern among Orientalist scholars challenging the authenticity of Islam. Clinton Bennett, a Christian theologian, presents himself as a Western academic adopting an independent stance in evaluating the rationale behind Muhammad’s teachings. While acknowledging the canonical status of Sahih al-Bukhari, Bennett questions the reliability of Abu Hurairah as a hadith transmitter, arguing that the honorific title Amir al-Muʾminin is inappropriate for a narrator of misogynistic traditions. His critique aligns with feminist scholar Fatima Mernissi’s gender-sensitive readings, particularly her concerns regarding the authenticity of certain historical narratives. A prominent example is Abu Hurairah’s narration of a woman condemned to hell for neglecting a female cat, an account interpreted as symptomatic of misogynistic tendencies within Islamic tradition. This study explores the authenticity of such a hadith and its implications for understanding misogyny in Islamic discourse through an inclusive and analytical lens. Employing a qualitative, descriptive-analytical method, it addresses the following question: How do Orientalist and feminist methodologies evaluate the authenticity of misogynistic hadiths in relation to Abu Hurairah’s credibility? The findings reveal that both Bennett and Mernissi assess Abu Hurairah’s reliability through a historical-critical framework, focusing on his age, proximity to the Prophet, and personal character. Their shared conclusion positions him as a junior companion whose close access to the Prophet arguably enabled a more consistent and guided transmission of hadiths.